Management Enhancement of Satuan Intelkam in Early Detection to Prevent Radicalism in the Jurisdiction of Demak Regional Police - Santosa, Samudra Kurniawan (Advances in Police Science Research Journal, 2024)
The goal of this study is to answer the writer's problem of why Satuan Intelkam's early detection in order to prevent radicalism wasn't optimal. In this research, the writer will describe the human resource and early detection method in order to prevent radicalism in Demak regional police jurisdiction. This study uses a qualitative approach. data gathered by the writer have descriptive characteristics so the writer uses interviews, observation, and documentary studies as a data-gathering technic. The focus of this research is the management of Satuan Intelkam’s early detection especially in Unit 4 Kamneg. Primary data was gathered by doing interviews with 10 people and secondary data was gathered by scripts. Data validation uses source, method, and theory triangulation. The results of this study indicate that the management of early detection analysed with human resource theory, management theory, Perkabik No. 1 Tahun 2013, Perpol No. 2 Tahun 2021 was not optimal. The human resources have a lack of quantity and quality as well as a less precise method that causes Satuan Intelkam’s early detection in order to prevent radicalism in Demak regional police jurisdiction wasn’t optimal.